Do autismo nos tempos do capitalismo ao sujeito autista da psicanálise (2012)
ABSTRACT: Over history, various discourses have determined the relations between subjects, their illness forms, and the disciplines dealing with them. Nowadays, science and capitalism are at the social zenith, signi0cantly in/uencing disciplines such as psychiatry and psychology, which today present themselves as those capable of responding to the ideals of a “scienti0c discourse” that seeks to produce results in a short period of time by means of homogenizing treatments. When addressing autism, cognitive-behavioral therapies are those that comply with the requirements of “scienti0cism” and, besides, by cataloging autism as a “disorder”, they provide the child, through the hands of psychiatry, with a large amount of psychotropic drugs aimed at making the autistic people “more normal, more adapted”. Psychoanalysis, on its turn, does not treat autism, but every autistic person, recognizing her/him as a subject, unique and singular. 5is text aims to review the speci0city of the psychoanalytic approach to autism in times when capitalism and science rule the social bond.